Pengaruh Conveyor Transfer Part Terhadap Waktu Tunggu dI Aktifitas Wheelblasting dan Spray - Fendri Yanto (Universitas Putera Batam, 2018)
This research is motivated by frequently some employees in process wheelblasting and Spray in idle state. After analyzed, it can be identified that the amount of idle time is aused by the material transfer process (Soleplate) which is still done manually which takes 18.5 seconds per unit (bottleneck). the purpose of this study are: To determine whether the conveyor can reduce waiting time in the Steam Promoter line or not. In this study, the anthropometry method used to determine the height of the conveyor and Westinghouse method is used to determine the magnitude of the rating factor and the amount of allowance. The results of this research are: a) The most ideal conveyor height is 90cm b) standard time of manual transfer (before improvement) is 28.55 seconds, c) standard transfer time using conveyor (after improvement) is 17.43 seconds, d) The difference of Standard time using manual transport Vs using conveyor is 11,12 second, e) by using conveyor, waiting time can be reduced.